Análise estrutural de halogenases encontradas em clusters gênicos da biossíntese de antibióticos glicopeptídicos - Cardoso, Tábata Peres [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Various experiments have shown that natural compounds may have their biologic activity altered by presence or absence of halogens. Glycopeptide antibiotics, such as vancomycin and teicoplanin are halogenated natural products and they have substantial importance in the medicine. Halogenases, are enzymes that catalyses the attachment of halogens to a substrate, howerver they are not well understood mainly those ones in glycopeptide biosynthesis. Producing glycopeptides strains were obtained from NRRL collection, they were grown in liquid TSB medium and the DNA was extracted. Three different genes for halogenases [(staI and staK from Streptomyces toyocaensis (compound 47934) and Orf8* from Actinoplanes teichomyceticus (Teicoplanin)] were amplified and cloned into pET28a and pET20a. A synthetic gene for comH from the biosynthesis of complestatin was obtained and also cloned in the pET28a. The expression of these four genes was carried out with the induction by IPTG and the purification was performed by affinity and molecular exclusion. Samples of soluble and insoluble fractions and chromatographic peaks were analyzed on SDS-PAGE gel. Circular Dichroism (CD) and Dynamic Light Scattering (DLS) studies were performed for StaI and ComH. We have also performed molecular modelling for StaI and StaK enzymes because attempts to crystallise all the soluble halogenases did not return any result (only StaI had a single crystal which showed not reproduzible). ComH, StaI and StaK were purified and they had an yellow colour indicating the co-purification with FAD.Orf8* was predominantly insoluble. SDS-PAGE gel showed that StaI had high purity already after the affinity purification and the molecular exclusion indicates that it had a tendency to aggregate. By the analysis of CD was possible to observe the structural integrity of StaI and ComH, which shows, as expected, the presence of -helixes and β-sheets. The DLS analysis shows the oligomerization ...

Vários experimentos têm comprovado que compostos naturais podem ter sua atividade biológica alterada devido à presença ou ausência de halogênios ligados. Os antibióticos glicopeptídicos, como a vancomicina e teicoplanina são produtos naturais halogenados que apresentam destacada importância. Halogenases são enzimas que catalizam a transferência de halogênios para um determinado substrato, porém são muito pouco estudadas, principalmente aquelas envolvidas na biossíntese de produtos naturais, como antibióticos glicopeptídicos, mesmo com o seu potencial de aplicação em biologia sintética. Cepas produtoras de glicopeptideos foram obtidas da coleção NRRL e crescidas em meio TSB. O DNA foi extraído e os genes de 3 diferentes halogenases (staI e staK de Streptomyces toyocaensis, composto 47934 and Orf8* de Actinoplanes teichomyceticus, Teicoplanina) foram clonados em pET28a e pET20a. Um gene sintético foi obtido para enzima ComH (biossíntese de complestatina) e clonado em pET28a. A expressão desses genes foi induzida por IPTG e a purificação se deu em colunas de afinidade e gel filtração. Foram realizados estudos biofísicos (CD e DLS da StaI), bem como modelagem molecular e ensaios de complementação para proteínas StaK e StaI. Três halogenases foram purificadas, StaI, StaK e ComH e apresentaram coloração amarela indicando a co-purificação com FAD. Orf8* apresentou-se somente na fração insolúvel. Análises de CD indicam a presença de -hélices e folhas-β e foi possível observar o estado de oligomerização e polidispersividade em diferentes condições para halogenase StaI. Os modelos moleculares deram insights sobre uma possível diferença de padrão de halogenação catalizada pela StaI e StaK, devido à diferença de resíduos hidrofóbicos que formam os sulcos do sítio ativo. Tentativas de ensaios de cristalização para as enzimas StaI, StaK e ComH foram realizadas. No entanto, apenas a...
Keywords: Microbiologia médica; Anti-infecciosos; Streptomyces; Compostos organo-halogenados; Produtos naturais; Expressão gênica; Medical microbiology